Head and neck injuries in professional soccer - Nilsson, M.; Hägglund, M.; Ekstrand, J.; Walden, M. (Clinical Journal of Sport Medicine, 2013)
Objective: To investigate the rate of and risk factors for head and neck injury in male soccer.